Understanding the Dynamics of Female Bullying - Rilveria, Loida (Bina Nusantara University, 2023)
The research aimed to explain the dynamics of female bullying and its causes and characteristics. Bullyingâ€™s influence on schools and society was becoming a growing problem; it affected the person being bullied and the bully, which might lead to anxiety, depression, sleep issues, decreased academic success, and school dropout and more likely to attempt suicide. With this, many types of research were conducted to identify factors surrounding bullying; however, it lacked research converging on female bullying. Female bullying might not exist for many, but it was considered more dangerous than male bullying because it attacked its victims in social and psychological aspects, causing them to seek vengeance or, worse, attempt suicide. The research applied a qualitative research method corresponding to a case study design. Qualitative data consisted of open-ended information gathered through interviews and observation. It is found that the causes of female bullying are identity crisis, family and social alienation, bullying experiences, overwhelming emotions, and a low tolerance for other peopleâ€™s physical appearance or characteristics. It further discloses that female bullying usually uses subtle attacks in verbal bullying, physical bullying, and social bullying, which characterizes it from any other form of bullying.Â